Regional grants as pork barrel politics - Kevin Milligan; Michael Smart (Center for Economic Studies and ifo Institute (CESifo), 2005)
We investigate the political and economic factors influencing the allocation of regional development grants for a panel of Canadian electoral districts in the 1988-2001 period. In a strong party system such as Canada's, models of political competition predict little role for individual legislators, as party leaders allocate resources to maximize party success. While spending is targeted toward some 'swing? districts, we do also find it is higher in districts represented by members of the government party, especially those in the federal Cabinet, and those of lower seniority. We develop a model featuring bargaining over legislative and nonlegislative favours that is consistent with the evidence.
Keywords: H25; D72; R58; 330; Regionalpolitik; Regierung; Verhandlungen; Public Choice; Kanada